2010
DOI: 10.1161/circulationaha.109.927764
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Myocardial Hypertrophy After Aortic Valve Replacement

Abstract: Background-In patients with aortic stenosis, pressure overload induces cardiac hypertrophy and fibrosis. Female sex and estrogens influence cardiac remodeling and fibrosis in animal models and in men. Sex differences and their molecular mechanisms in hypertrophy regression after aortic valve replacement have not yet been studied. Methods and Results-We prospectively obtained preoperative and early postoperative echocardiography in 92 patients, 53 women and 39 men, undergoing aortic valve replacement for isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
156
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 211 publications
(172 citation statements)
references
References 26 publications
15
156
0
1
Order By: Relevance
“…So, the greater absolute LV mass regression seen in men was a result of the fact that men have more LV mass at baseline than their female counterparts, rather than a sex-related difference per se. Stangl et al found a better LVEF at baseline and a more favourable LV remodeling response in women upon serial echocardiography following TAVR, but their female population had higher pre-TAVR aortic valve gradients than men, which may explain the greater degree of mass regression seen 13 .In an echocardiographically based study of 92 patients undergoing SAVR for isolated AS, Petrov et al 14 found a similar LVMi at baseline in men and women, but a greater degree of LVM regression in women after SAVR. This study was based on measurements taken only 3 days post-SAVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the greater absolute LV mass regression seen in men was a result of the fact that men have more LV mass at baseline than their female counterparts, rather than a sex-related difference per se. Stangl et al found a better LVEF at baseline and a more favourable LV remodeling response in women upon serial echocardiography following TAVR, but their female population had higher pre-TAVR aortic valve gradients than men, which may explain the greater degree of mass regression seen 13 .In an echocardiographically based study of 92 patients undergoing SAVR for isolated AS, Petrov et al 14 found a similar LVMi at baseline in men and women, but a greater degree of LVM regression in women after SAVR. This study was based on measurements taken only 3 days post-SAVR.…”
Section: Discussionmentioning
confidence: 99%
“…suggest that men and women remodel differently to the pressure overload of AS 11,12 and may also reverse remodel differently following AVR 13,14 . CMR imaging is the reference standard for LV mass and volume quantitation, with low intra-observer and inter-study variability.…”
Section: Fibrosis (Mf) May Be Implicated Echocardiographic and Cardimentioning
confidence: 99%
“…27 Our own investigations showed increased levels of collagens I and III, as well as matrix metalloproteinase (MMP) expression, in a cohort of predominantly male patients undergoing aortic valve surgery, 28,29 and greater upregulation of matrix-related genes in men than in women. 30 Relief of mechanical obstruction by aortic valve replacement led to hemodynamic improvement and a substantial decrease in LV mass in both sexes, but it occurred faster in women than in men. 30 Gene expression profiling in end-stage failing human hearts has revealed similar sex differences as found in animals with HF: less downregulation of energy metabolism in female hearts and more matrix induction in male hearts.…”
Section: Human Hearts: Sex Differences In Pathological Mhmentioning
confidence: 98%
“…30 Relief of mechanical obstruction by aortic valve replacement led to hemodynamic improvement and a substantial decrease in LV mass in both sexes, but it occurred faster in women than in men. 30 Gene expression profiling in end-stage failing human hearts has revealed similar sex differences as found in animals with HF: less downregulation of energy metabolism in female hearts and more matrix induction in male hearts. 31 …”
Section: Human Hearts: Sex Differences In Pathological Mhmentioning
confidence: 98%
“…39,40 Accordingly, mRNA for collagen I, collagen III, matrix metalloproteinase 2, and matrix metalloproteinase 9 was significantly higher in men than in women with AS ( Figure 4A). 41 Collagen gene expression was closely correlated with LVM ( Figure 4B), suggesting that both mechanisms, fibrosis and MH, are closely interrelated. established model of PO in the mouse.…”
Section: Sex Differences In Human Po and Hfmentioning
confidence: 86%